2005
DOI: 10.1681/asn.2004110930
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of Hypertonicity on Aquaporin-2 Expression in Cultured Renal Collecting Duct Principal Cells

Abstract: The driving force for renal water reabsorption is provided by the osmolarity gradient between the interstitium and the tubular lumen, which is subject to rapid physiologic variations as a consequence of water intake fluctuations. The effect of increased extracellular tonicity/osmolarity on vasopressin-inducible aquaporin-2 (AQP2) expression in immortalized mouse collecting duct principal cells (mpkCCD cl4 ) is investigated in this report. Increasing the osmolarity of the medium either by the addition of NaCl, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 43 publications
5
87
0
Order By: Relevance
“…Hyperosmolality has been shown to upregulate AQP2 in several in vitro cell culture systems (7,8), but, to date, the effect of increased osmolality in vivo to enhance AQP2 protein expression and trafficking remains to be documented clearly. In this regard, there have been conflicting results about the effects of fluid deprivation in BB rats to alter AQP2 expression (19,22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperosmolality has been shown to upregulate AQP2 in several in vitro cell culture systems (7,8), but, to date, the effect of increased osmolality in vivo to enhance AQP2 protein expression and trafficking remains to be documented clearly. In this regard, there have been conflicting results about the effects of fluid deprivation in BB rats to alter AQP2 expression (19,22).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperosmolality also increased the expression of AQP3 in vitro (6). In recent in vitro studies, a long-term (24 h) increase of extracellular tonicity by addition of NaCl or sucrose increased AQP2 expression via stimulation of AQP2 gene transcription (7). In mouse inner medullary CD mIMCD3 cell lines that were transfected with AQP2 cDNA, hyperosmolality with supplemented NaCl increased the expression of nonglycosylated AQP2 and enhanced the apical membrane insertion of nonglycosylated AQP2 in the absence of AVP.…”
mentioning
confidence: 84%
“…Cell lysates were prepared and quantified as described previously (78). Actin polymerization was quantified by determining the Triton X-100-soluble (G-actin)/TritonX-100-insoluble (F-actin) ratio.…”
Section: Measurement Of Relative Changes In [Clmentioning
confidence: 99%
“…Hypertonicity has also been shown to trigger the translocation of AQPs 1, 2, 3, 4, 5 and 9 (Arima et al, 2003, Hasler et al, 2005, Hoffert et al, 2000, Loitto et al, 2007, Matsuzaki et al, 2001) whilst hypotonicity has been shown to be involved in translocation of AQPs 1, 3 and 8 (Conner et al, 2012, Conner et al, 2010, Garcia et al, 2011, Qi et al, 2009 (Table 2).…”
Section: What Triggers Aqp Translocation?mentioning
confidence: 99%